Genome-wide characterization of C2H2 zinc-finger gene family provides insight into the mechanisms and evolution of the dehydration–rehydration responses in Physcomitrium and Arabidopsis - Li, Xuan; Cao, Xubing; Li, Jialing; Niu, Qinqin; Mo, Yuanping; Xiao, Lihong (Frontiers in Plant Science, 2022)
Dehydration tolerance is a vital factor for land plant evolution and world agricultural production. Numerous studies enlightened that the plant-specific C2H2-type zinc finger proteins (C2H2-ZFPs) as master regulators played pivotal roles in abiotic stress responses of plants. However, a comprehensive understanding of the evolution of C2H2-ZFPs in terrestrial plants and its regulatory mechanism in dehydration and rehydration response remains a mystery. In this study, the genome-wide identification of C2H2-ZFP genes revealed 549 homologs in the representatives of terrestrial plant lineages from liverwort to angiosperms. Based on the characteristics of the conserved C2H2-ZF domains, four major C2H2-ZF types (M-, Z-, Q- and D-type) were identified in the C2H2-ZFPs, with the dominants of M-type in all selected species and followed by Z-type in non-seed plants and Q-type in seed plants, respectively. Phylogenetic analyses of the identified C2H2-ZFPs supported four major -groups in the land plant representatives, among which the members from the desiccation-tolerant Physcomitrium patens and the dehydration-sensitive Arabidopsis thaliana displayed different topological relationships in the phylogenies reconstructed for a single species. C2H2-ZFPs clustered in the same subclades shared similar features in their conserved domains and gene structures. Approximately 81% of the C2H2-ZFP promoters of all 549 identified C2H2-ZFPs harbored the conserved ABA-responsive (ABREs) and/or dehydration-responsive elements (DREs). Comparative transcriptomic analyses showed that 50 PpZFPs and 56 AtZFPs significantly changed their transcripts abundance. Interestingly, most of the dehydration and rehydration responsive PpZPFs and AtZFPs had been predicted to contain the ABRE and DRE elements in their promoter regions and with over half of which phylogenetically belonging to group III. The differences in the expression patterns of C2H2-ZFPs in responses to dehydration and rehydration between P. patens and A. thaliana, reflected their different strategies to adapt to dehydration. The identified candidate PpZFPs were specifically induced by moderate dehydration and reached the peak transcript abundance in severe dehydration. Our study lays the foundations for further functional investigation of C2H2-ZFPs in dehydration responses from an evolutionary perspective in land plants. The findings will provide us with genetic resources and potential targets for drought tolerance breeding in crops and beyond.